Fluktuasi Populasi dan Keragaman Musuh Alami Hama Wereng Batang Coklat (Nilaparvata lugens Stal.) pada Lahan Padi Sawah di Wilayah Universitas Wiralodra, Kabupaten Indramayu, Jawa Barat - Martua Suhunan Sianipar (Agrikultura, 2018)
ABSTRACTPopulation fluctuation and natural enemy diversity of brown planthopper (Nilaparvata lugens Stal.) in the rice lowlands of Wiralodra University Area, Indramayu Regency, West JavaBrown Planthopper/BPH (Nilaparvata lugens Stal.) is a main pest of paddy. The purpose of this research was to study the population fluctuation and natural enemy diversity of BPH in rice plants. The research was carried out with a survey method conducted on three experimental lands located in the lowlands of Wiralodra University, Singaraja Village, Indramayu District, Indramayu Regency, West Java and in the greenhouse of the Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Padjadjaran from June to August 2015. The samples were collected by systematically diagonal sampling method using yellow stiky trap and manually or visual counting. The result showed that the BPH population fluctuations were below BPH economic threshold the results of correlation analysis showed that temperature, humidity and rainfall did not have a significant influence on the abundance of the BPH population. This is indicated by the results of regression analysis of temperature (Y = - 49.9 + 1.71 X1; R2 = 0.055; P/Sign = 0.484), humidity (Y = - 41.829 + 0.598 X2; R2 = 0.457; P/Sign = 0.016), and rainfall (Y = 2.845 + 0.512 X3; R2 = 0.217; P/Sign = 0.127), respectively. The relationship between temperature/T, humidity/RH and rainfall/CH on WBC (Y = - 94.2 + 3.00 T + 0.002 RH + 0.804 CH; R2 = 0.581; P/ ign = 0.062) had a significance level > 0.05. The natural enemy insect diversity index was in the medium category (1.63).Keywords: BPH, Abiotic factor, Natural Enemy, Lowland riceABSTRAKWereng Batang Cokat/WBC (Nilaparvata lugens Stal.) merupakan hama utama tanaman padi. Penelitian ini bertujuan untuk mempelajari fluktuasi populasi serta keragaman musuh alami WBC pada tanaman padi. Penelitian ini dilakukan dengan metode survei yang dilakukan pada tiga lahan percobaan yang bertempat dataran rendah di wilayah Universitas Wiralodra, Desa Singaraja, Kecamatan Indramayu, Kabupaten Indramayu, Jawa Barat dan di rumah kaca Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran pada bulan Juni sampai Agustus 2015. Metode pengambilan sampel dilakukan secara diagonal menggunakan perangkap kuning berperekat (yellow stiky trap) serta secara manual (visual counting). Hasil penelitian menunjukkan fluktuasi populasi WBC berada di bawah ambang ekonomi WBC dan hasil analisa korelasi menunjukkan suhu, kelembaban dan curah hujan tidak memberikan pengaruh yang signifikan terhadap kelimpahan populasi WBC. Hal ini ditunjukkan dengan hasil analisis regresi masing-masing pada suhu (Y = - 49.9 + 1.71 X1; R2 = 0,055; P/Sign = 0,484), kelembaban (Y= - 41.829 + 0.598 X2; R2 = 0,457; P/Sign = 0,016) dan curah hujan (Y = 2.845 + 0.512 X3; R2 = 0,217; P/Sign = 0,127). Adapun hubungan antara Suhu/T, Kelembaban/RH dan Curah Hujan/CH terhadap WBC (Y = - 94.2 + 3.00 T + 0.002 RH + 0.804 CH; R2 = 0.581; P/Sign = 0.062) memiliki tingkat signifikansi > 0,05. Indeks keragaman serangga musuh alami WBC termasuk kategori sedang (1,63).Kata Kunci: WBC, Fakor Abiotik, Musuh alami, Lahan sawah